A novel stibacarbaborane cluster with adjacent antimony atoms exhibiting unique pnictogen bond formation that dominates its crystal packing. Issue 40 (28th September 2017) - Holub, Josef; Melichar, Petr; Růžičková, Zdeňka; Vrána, Jan; Wann, Derek A.; Fanfrlík, Jindřich; Hnyk, Drahomír; Růžička, Aleš
Abstract : The reaction of arachno -4, 6-C2 B7 H13 with SbCl3 yields nido -7, 8, 9, 11-Sb2 C2 B7 H9, which simultaneously has Sb–Sb, Sb–B and Sb–C bonds and a unique ability to form pnictogen bonds. Abstract : We have prepared nido -7, 8, 9, 11-Sb2 C2 B7 H9, the first cluster with simultaneous Sb–B, Sb–C and Sb–Sb atom pairs with interatomic separations with magnitudes that approach the respective sums of covalent radii. However, the length of the Sb–Sb separation in this cluster is slightly less than the sum of the covalent radii. Quantum chemical analysis has revealed that the crystal packing of nido -7, 8, 9, 11-Sb2 C2 B7 H9 is predominantly dictated by pnictogen (Pn) bonding, an unconventional σ-hole interaction. Indeed, the interaction energy of a very strong Sb2 ⋯H–B Pn-bond in the nido -7, 8, 9, 11-Sb2 C2 B7 H9 dimer exceeds −6.0 kcal mol −1 . This is a very large value and is comparable to the strengths of known Pn-bonds in Cl3 Pn⋯π complexes (Pn = As, Sb).